2006
DOI: 10.1111/j.1600-0625.2006.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectral karyotyping demonstrates genetically unstable skin‐homing T lymphocytes in cutaneous T‐cell lymphoma

Abstract: We initially established cell lines from skin biopsies from four patients (MF8, MF18, MF19 and MF31) in early stages of cutaneous T-cell lymphoma (CTCL) in 1999. After 3 weeks of culture, skin-homing T lymphocytes were stimulated with phytohaemagglutinin. Metaphase spreads were analysed using spectral karyotyping (SKY), a molecular cytogenetic technique. MF18 and MF19 had predominantly normal karyotypes. MF8 had recurrent numerical aberrations resulting in two T lymphocyte clones: one with trisomy 21 (12/20 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…We observed that many cells in the cell strains underwent quite dramatic changes, including deletions, translocations and extra chromosomes (18,19). although no unifonn pattern was observed, as confirmed by others (20).…”
Section: Discussionsupporting
confidence: 87%
“…We observed that many cells in the cell strains underwent quite dramatic changes, including deletions, translocations and extra chromosomes (18,19). although no unifonn pattern was observed, as confirmed by others (20).…”
Section: Discussionsupporting
confidence: 87%
“…Mutations or expression changes in the molecules that retain T cells in skin could give rise to malignant T cells that can access and accumulate within the circulation. Alternatively, patients with CTCL have been known to develop multiple different malignant T cell clones, arguing that genetic damage and genomic destabilization occur in a group of T cells, some of which give rise to overtly malignant T cell clones ( 22, 37 ). Peripheral blood disease in patients with long-standing stable MF could also be caused by two distinct T cell clones.…”
Section: Discussionmentioning
confidence: 99%
“…Metaphase spread was performed as described (21). Briefly, HeLa cells were gently suspended in 75 m m KCl and incubated at room temperature for 25 min.…”
Section: Methodsmentioning
confidence: 99%